Inorganic Lead‐Free Cs2AuBiCl6 Perovskite Absorber and Cu2O Hole Transport Material Based Single‐Junction Solar Cells with 22.18% Power Conversion Efficiency. Issue 3 (1st February 2021) - Kale, Abhijeet J.; Chaurasiya, Rajneesh; Dixit, Ambesh
Abstract: Cs2 AuBiCl6 is considered to be a potential lead‐free double perovskite alternative for perovskite solar cells. Its electronic and optical properties are investigated using density functional theory. The electronic properties of Cs2 AuBiCl6 material ensure a bandgap of 1.40 eV (without considering SOC) and 1.12 eV (with SOC) using mBJ exchange‐correlation functional, close to the optimal bandgap for solar cell application as per the Shockley–Queisser limit. Optical properties suggest a high absorption coefficient ≈10 5 cm −1 with low reflectance, making it the optimal absorber material. Furthermore, the photovoltaic performance of Cs2 AuBiCl6 based single‐junction transparent conducting oxide (TCO)/IDL1/Cs2 AuBiCl6 /IDL2/Cu2 O solar cell is investigated using SCAPS‐1D device simulation program. The impact of electron affinity, thickness, carrier concentration, defect density, and interface defect density is examined using interface defect layer (IDL) on the photovoltaic performance. The maximum photoconversion efficiency (PCE) of ≈22.18% is noticed for optimized material's parameters. These studies on TCO/IDL1/Cs2 AuBiCl6 /IDL2/Cu2 O solar cell will provide guidelines for designing and developing an efficient lead‐free perovskite‐based solar cell as an alternative to conventional halide perovskite materials based solar cell. Abstract : A lead‐free double perovskite solar cell: this study uncovers the promise of new double perovskite for use in a lead‐free solar cell. Density functional theory (DFT‐) based studies together with spin–orbit coupling suggests Cs2 AuBiCl6 as a potential solar absorber material. This absorber with Cu2 O as the hole transport material shows 22.18% photovoltaic efficiency.